Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae) - Bramuzzo, Simone; Nel, André (Zootaxa, 2017)
Prior to the present study, seven species of the fossil microphorine (Dolichopodidae s. lat.) genus Microphorites Hennig, 1971 have been described: Microphorites extinctus Hennig, 1971 (type species), M. oculeus Grimaldi & Cumming, 1999, and M. similis Grimaldi & Cumming, 1999 (all from the Early Cretaceous Lebanese amber), M. deploegi Nel et al., 2004 (from the Early Cretaceous of France), M. utrillensis Peñalver, 2008 (from the Early Cretaceous amber of Spain), M. magaliae Perrichot & Engel, 2014 (from the Late Cretaceous amber of France), M. moravicus Tkoč et al., 2016 (possibly from the Paleogene amber of Moravia) (Hennig 1971; Grimaldi & Cumming 1999; Nel et al. 2004; Arillo et al. 2008; Perrichot & Engel 2014; Tkoč et al. 2016). Based on the dating of these amber species, Microphorites could be among the rare insect genera recorded from both the Cretaceous and the Paleogene. Here we describe Microphorites erikai sp. nov., first accurate Eocene Microphorites from the Oise amber (France), on the basis of a complete female specimen.